The impact of remote working on job satisfaction - Nguyen, Khanh Linh; Černá, Daniela; Legnerová, Kateřina, 1965-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
The aim of this thesis is to provide the reader with a deeper understanding and acquire knowledge of the concept of motivation associated with job satisfaction among Generation Z employees in the remote working environment. The thesis is divided into two main parts. In the theoretical part, the author reviews the literature, including the key terms. Explains factors affecting motivation and job satisfaction. Additionally, discuss the concept of remote working and the different components of remote working influencing the level of job satisfaction. The practical part of the thesis answers the research questions. Subsequently, the data was collected through semi-structured in-depth interviews. A qualitative research method was chosen to help the author understand the topic of interest.
Vedoucí práce: Daniela Černá
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses